2003
DOI: 10.1038/sj.bjc.6601331
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of immune cell infiltration within gallbladder cancer

Abstract: To investigate the pathophysiological significance of infiltrating antitumour immune cells, we evaluated the quantity of immune cell intratumoral infiltration in 110 surgically resected gallbladder specimens by immunohistochemistry. We examined 45 cases of gallbladder cancer and 65 cases of benign gallbladder diseases for CD4 þ T cells, CD8 þ T cells, natural killer cells (NKCs), and dendritic cells (DCs). High levels of CD4 þ T cell, CD8 þ T cell, NKC, and DC infiltration were recognised in 51.1% (23 out of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 27 publications
(37 reference statements)
1
67
0
2
Order By: Relevance
“…oesophageal squamous cell carcinoma Nakakubo et al, 2003;Oshikiri et al, 2003;Fukunaga et al, 2004). However, in NSCLC, the role of TILs for the survival of patients is still controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…oesophageal squamous cell carcinoma Nakakubo et al, 2003;Oshikiri et al, 2003;Fukunaga et al, 2004). However, in NSCLC, the role of TILs for the survival of patients is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Among TILs, most CD8 þ T cells are cytotoxic T lymphocytes that recognise particular tumour-associated antigens presented on MHC class I molecules at the cancer cell surface and possess the ability to destroy cancer cells directly. The favourable prognostic significance of the presence of tumour-infiltrating CD8 þ T cells was previously reported in a variety of cancers, including colorectal cancer, oesophageal cancer, pancreatic cancer, bile duct cancer and gallbladder cancer (Naito et al, 1998;Nakano et al, 2001;Schumacher et al, 2001;Cho et al, 2003;Nakakubo et al, 2003;Oshikiri et al, 2003;Fukunaga et al, 2004). In NSCLC, however, the relationship between patient prognosis and the presence of TILs is still obscure.…”
mentioning
confidence: 92%
“…Indirect evidence suggests that T cell immunity may participate in controlling disease progression for GI adenocarcinomas arising in the esophagus, stomach, pancreas, liver, bile ducts, gallbladder, colon, and rectum (10)(11)(12)(13)(14)(15)(16)(17)(18). A redefinition of prognostic staging is being proposed based on the density of the TILs found in primary tumors, among which colorectal cancer has been studied most extensively (19).…”
mentioning
confidence: 99%
“…Published studies have indicated differences in number of tumor-infiltrating immune cells among broad age groups in some solid malignancies. 19,[24][25][26][27] However, these studies were not designed with the explicit purpose of evaluating immune cell infiltration with a specific focus on older patients.…”
Section: Discussionmentioning
confidence: 99%